Calcium‐binding protein expression in peritoneal endometriosis‐associated nerve fibres. (6th May 2013) - Barcena de Arellano, M. L.; Münch, S.; Arnold, J.; Helbig, S.; Schneider, A.; Mechsner, S.
Abstract Background Recent studies demonstrated the potential involvement of nerve fibres in the chronic inflammatory process of endometriosis. We aimed to characterize nerve fibres in the proximal and distal areas of the peritoneal endometriotic lesions in order to understand the chronic inflammatory process in endometriosis. Methods Peritoneal endometriotic lesions (proximal area) (n = 17), the matching unaffected peritoneum (distal area) and healthy peritoneum of patients without endometriosis (n = 15) were analysed with the neuronal markers PGP 9.5, calbindin, calretinin and parvalbumin. Peritoneal fluids of women with and without endometriosis were used for Western blot analysis and for the neuronal growth assay. The protein expression of neuronal PC‐12 cells incubated with peritoneal fluids was analysed. Results The overall nerve fibre density was significantly reduced in the distal area of the lesion when compared with the proximal area or with healthy peritoneum. The density of calbindin‐, calretinin‐ and parvalbumin‐positive nerve fibres was significantly increased in the endometriosis group. Calretinin expression was elevated in the peritoneal fluid of women with symptomatic endometriosis when compared with women with asymptomatic endometriosis. Furthermore, PC‐12 cells incubated with peritoneal fluid of women with endometriosis showed a higher proliferation rate and a stronger neurite outgrowth than the control group. PC‐12 cells incubated in peritoneal fluids of women with endometriosis expressed less calretinin but more calbindin than the control group. Conclusions Calcium‐binding proteins seem to be increased in endometriosis‐associated nerve fibres and might play an important role in the chronic inflammatory condition and the pain pathogenesis of endometriosis.